TRANSLATING TECHNIQUES AND STRATEGIES OF CULTURAL TERMS IN SIMULTANEOUS INTERPRETATION (Academicia Globe: Inderscience Research, 2023)
Simultaneous interpretation is a complex task that involves conveying messages from one language to another in real-time. Cultural terms, which are deeply rooted in specific cultures, pose a significant challenge to interpreters. This article explores the techniques and strategies employed in translating cultural terms during simultaneous interpretation. The study aims to provide insights into the linguistic and cultural considerations that interpreters must navigate to ensure accurate and culturally appropriate communication.